KAJIAN YURIDIS TRANSAKSI DERIVATIF KONTRAK BERJANGKA DALAM BURSA EFEK INDONESIA - Jeremia Raharja (Universitas Katolik Indonesia Atma Jaya, 2019)
Derivative trading is a form of trading that moves fast (fast moving), in large numbers (high volume) and with a high level of liquidity (free following liquid activity). Initially, derivative transactions attracted the interests of companies in the world because they could generate huge profits while also serving as a means of hedging. However, at present the boundary between the use of derivative transactions in Indonesia as a means of hedging and a means for speculating for huge profits has not been confirmed. This is because the use of derivative transactions to seek large profits has the potential to also get very large losses. A concrete example of the impact of derivative transactions can be seen in the collapse of Baring Bank, the oldest bank in the UK to go bankrupt due to derivative transactions carried out by a manager. Therefore in the use of derivative transactions as a means of hedging and a means of profit speculation there must be a clear and explicit distinction. From 2001 to 2009 derivative products were stopped by the Indonesia Stock Exchange (IDX), this was due to less dynamic trading. Beginning in 2016, the IDX announced the reactivation of trading in derivative products based on the Securities Index-based Futures Contract (KBIE) namely LQ-45 (LQ-45 Futures Index). There are two derivative products that will actually be present in the Indonesian stock market, namely futures contracts and stock options. But for now, the only derivative product on the Indonesian stock market is the LQ-45 stock index futures contract.